2018
DOI: 10.3390/polym10060571
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of New Pervaporation PVA Membranes for the Dehydration Using Bulk and Surface Modifications

Abstract: In the present work, the novel dense and supported membranes based on polyvinyl alcohol (PVA) with improved transport properties were developed by bulk and surface modifications. Bulk modification included the blending of PVA with chitosan (CS) and the creation of a mixed-matrix membrane by introduction of fullerenol. This significantly altered the internal structure of PVA membrane, which led to an increase in permeability with high selectivity to water. Surface modification of the developed modified dense me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Namboodiri et al [32,33] developed new dense membranes based on mixtures of poly(allylamine hydrochloride)-poly(vinyl alcohol) cross-linked by glutaraldehyde (GA) for the pervaporation dehydration of various organic solvents such as ethanol, methanol, acetone, and isopropanol. They incorporated PVA into the PAH matrix at various formulation ratios to get improved membrane characteristics, such as flexibility and stability.Our previous studies [23,35] showed that many parameters could be used to tune the PEL effect on the transport characteristics of the PVA membranes, such as the selected pair of polycation-polyanion, the order of their deposition via the LbL deposition technique, the number of cycles, and additional bulk modification (introduction of PAH or CS). Thus, a PVA-fullerenol membrane modified by PAH (4.7 wt %) exhibited the best transport properties for the dehydration of isopropanol after an additional surface modification by 10 bilayers of poly(sodium 4-styrenesulfonate) (PSS)/PAH, which led to an increase in the permeation flux (0.29 kg/(m 2 h)) with a high level of selectivity (water content in the permeate was 98.4 wt %) [23].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Namboodiri et al [32,33] developed new dense membranes based on mixtures of poly(allylamine hydrochloride)-poly(vinyl alcohol) cross-linked by glutaraldehyde (GA) for the pervaporation dehydration of various organic solvents such as ethanol, methanol, acetone, and isopropanol. They incorporated PVA into the PAH matrix at various formulation ratios to get improved membrane characteristics, such as flexibility and stability.Our previous studies [23,35] showed that many parameters could be used to tune the PEL effect on the transport characteristics of the PVA membranes, such as the selected pair of polycation-polyanion, the order of their deposition via the LbL deposition technique, the number of cycles, and additional bulk modification (introduction of PAH or CS). Thus, a PVA-fullerenol membrane modified by PAH (4.7 wt %) exhibited the best transport properties for the dehydration of isopropanol after an additional surface modification by 10 bilayers of poly(sodium 4-styrenesulfonate) (PSS)/PAH, which led to an increase in the permeation flux (0.29 kg/(m 2 h)) with a high level of selectivity (water content in the permeate was 98.4 wt %) [23].…”
mentioning
confidence: 99%
“…On the other hand, the use of porous substrate based on polyethyleneterephthalate with polyacrylonitrile resulted in a limitation of the stability in water of the deposited PSS/PAH nanolayers (up to 20 wt % water in the feed) and the limitation of the number of PEL bilayers (from 15 bilayers) [36]. It should be noted that, in References [23,35], the effect of PAH introduction into the PVA matrix and the interaction nature between PAH and PVA were not provided. Moreover, the selectivity properties of the best PVA-fullerenol (5%)-PAH/LbL-10 membrane could be improved (98.4%).The aim of this work was to study dense and supported pervaporation PVA-based membranes modified with poly(allylamine hydrochloride) (PAH) and PSS/PAH top nanolayers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bulk modification involves the insertion of functional groups into the membrane matrix to improve certain characteristics of the IEM. This method can be achieved by blending two or more polymers in different concentration ratios to obtain the desired membrane properties [12,13,65]. Stability, permselectivity, and conductivity of IEM can be controlled by tuning the hydrophobic and hydrophilic properties of the blend membrane [66].…”
Section: Bulk Modificationmentioning
confidence: 99%
“…Among these, PVA is considered to be one of the most widely used polymers in pervaporation, applied for the separation of water-organic mixtures, due to its unique properties such as good film-forming properties, high hydrophilicity, and chemical stability. However, the permeability of PVA-based membranes is too low due to its glassy and semi-crystalline structure [3]. Polyvinyl alcohol (PVA) as biodegradable polymer can be used in numerous applications attributable to its specific properties such as good fiber forming, good thermal and chemical stability along with high tensile and impact strengths.…”
Section: Introductionmentioning
confidence: 99%